Cardiac Baroreflex, HRV, and Statistics: An Interdisciplinary Approach in Hypertension - Solaro, Nadia; Malacarne, Mara; Pagani, Massimo; Lucini, Daniela (Frontiers in Physiology, 2019)
Interests about the fine underpinnings of cardiovascular beat-by-beat variability have historical roots. Over the last decades, various aspects of the relationships between arterial pressure and heart period were taken as a proxy of the baroreflex in physiology and medicine, stimulating the interest of investigators in several interconnected scientific fields, in particular, bioengineering, neurophysiology, and clinical medicine. Studies of the overall system facilitated the emergence of a simplified negative (vagal) feedback model of the baroreflex and overshadowed the simultaneous interaction with excitatory, sympathetic positive-feedback mechanisms that would however better suit the model of a “paired antagonistic (parasympathetic/sympathetic) innervation of the internal organs.” From the bioengineering side, the simplicity of obtaining the series of subsequent RR intervals stimulated the analysis of beat-by-beat variations, providing a multitude of HRV indices (i.e., heart rate variability) considered as proxies of the underlying sympatho-vagal balance, and participating to the management of several important clinical conditions, such as hypertension. In this context, advanced statistical methods, used in an integrated manner and controlling for age and gender biases, might help shed new light on the relationship between cardiac baroreflex, assessed by the frequency domain index alpha, and the HRV indices with the varying of systolic arterial pressure (SAP) levels. The focus is also on a novel unitary Autonomic Nervous System Index (ANSI) built as a synthesis of HRV considering its three most informative proxies (RR, RR variance and the rest-stand difference in the normalized power of Low-Frequency variability component). Data from a relatively large set of healthy subjects (n=1154) with a broad range of SAP (from normal (n_Nt=778) to elevated (n_Ht=232)) show that, e.g., alpha and ANSI significantly correlate overall (r=0.523,p<.001), and that this correlation is lower in hypertensives (r=0.444,p<.001) and higher in pre-hypertensives (r=0.618,p<.001) than in normotensives (r=0.5,p<.001). That suggests the existence of curvilinear “umbrella” patterns that might better describe the effects of the SAP states on the relationships between baroreflex and HRV. By a mix of robust, non-parametric and resampling statistical techniques, we give empirical support to this study hypothesis and show that the pre-hypertensive group results at the apex/bottom in most of the studied trends.